Optogenetic Control of Neural Circuits in the Mongolian Gerbil - Keplinger, Stefan; Beiderbeck, Barbara; Michalakis, Stylianos; Biel, Martin; Grothe, Benedikt; Kunz, Lars (Frontiers in Cellular Neuroscience, 2018)
The Mongolian gerbil (Meriones unguiculatus) is widely used as a model organism for the human auditory system. Its hearing range is very similar to ours and it uses the same mechanisms for sound localization. The auditory circuits underlying these functions have been characterized. However, important mechanistic details are still under debate. To elucidate these issues, precise and reversible optogenetic manipulation of neuronal activity in this complex circuitry is required. However, genetic and genomic resources for the Mongolian gerbil are poorly developed. Here, we demonstrate a reliable gene delivery system using an AAV8(Y337F)-pseudotyped recombinant adeno-associated virus (AAV) 2-based vector in which the pan-neural human synapsin (hSyn) promoter drives neuron-specific expression of CatCH (Ca2+-permeable channelrhodopsin) or NpHR3.0 (Natronomonas pharaonis halorhodopsin). After stereotactic injection into the gerbil’s auditory brainstem (medial nucleus of the trapezoid body, dorsal nucleus of the lateral lemniscus) and midbrain [inferior colliculus (IC)], we characterized CatCH- and/or NpHR3.0-transduced neurons in acute brain slices by means of whole-cell patch-clamp recordings. As the response properties of optogenetic tools strongly depend on neuronal biophysics, this parameterization is crucial for their in vivo application. In a proof-of-principle experiment in anesthetized gerbils, we observed strong suppression of sound-evoked neural responses in the dorsal nucleus of the lateral lemniscus (DNLL) and IC upon light activation of NpHR3.0. The successful validation of gene delivery and optogenetic tools in the Mongolian gerbil paves the way for future studies of the auditory circuits in this model system.